2015
DOI: 10.1007/s11010-015-2379-1
|View full text |Cite
|
Sign up to set email alerts
|

Clopidogrel reduces apoptosis and promotes proliferation of human vascular endothelial cells induced by palmitic acid via suppression of the long non-coding RNA HIF1A-AS1 in vitro

Abstract: Cardiovascular disease (CVD) is recognized as a major and increasing health problem affected older subjects in China, and clopidogrel has been widely used for treatment of CVD patients such as atherosclerosis, myocardial infarction, and myocardial ischaemia-reperfusion damage. However, the molecular mechanisms of clopidogrel for treatment of CVD are only partially understood. This study investigated the effects of clopidogrel on palmitic acid-induced damage of human vascular endothelial cells (HUVECs), and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 28 publications
1
35
0
Order By: Relevance
“…Most strikingly, we observed that HIF1A-AS1, a recently characterized [34] long non-coding RNA (lncRNA) was downregulated in ECs only, when co-cultured with CMs. Although little is known about HIF1A-AS1, it was shown that suppression of HIF1A-AS1 by siRNA targeting reduced palmitic acid induced apoptosis and promoted proliferation in vascular smooth muscle cells [35, 36] and HUVECs [37] in vitro . The fact that we did not observe any changes in HIF-1α or PHD expression levels might suggest that HIF1A-AS1 may be an alternative means of HIF-1α regulation under oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Most strikingly, we observed that HIF1A-AS1, a recently characterized [34] long non-coding RNA (lncRNA) was downregulated in ECs only, when co-cultured with CMs. Although little is known about HIF1A-AS1, it was shown that suppression of HIF1A-AS1 by siRNA targeting reduced palmitic acid induced apoptosis and promoted proliferation in vascular smooth muscle cells [35, 36] and HUVECs [37] in vitro . The fact that we did not observe any changes in HIF-1α or PHD expression levels might suggest that HIF1A-AS1 may be an alternative means of HIF-1α regulation under oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Palmitic acid (PA) can impose damage to ECs, which is rescued by clopidogrel, an antiplatelet agent widely used for treating cardiovascular disease 95 . LncRNA HIF1α-AS1 was identified as a major lncRNA downregulated by clopidogrel treatment in ECs.…”
Section: Lncrnas In Vascular Diseasementioning
confidence: 99%
“…HIF1α -AS1 was initially identified in VSMCs, and its expression is dependent on BRG1 in VSMCs 97 . Silencing of HIF1α -AS1 has been shown to promote cell proliferation and reduce cell death in VSMCs 95 - 97 . SENCR is a lncRNA enriched in ECs and VSMCs 105 .…”
Section: Lncrnas In Vascular Diseasementioning
confidence: 99%
“…Furthermore, the T variant of rs217727 and the A variant of rs2067051 was associated with increased and decreased risk of CAD, respectively 78) . Moreover, several studies confirm that lncRNA HIF1A-AS1 knockdown decreases apoptosis and promote proliferation VSMC [79][80][81] , but whether it plays a role in atherosclerosis is yet unknown.…”
Section: Long Noncoding Rnas In Smcsmentioning
confidence: 99%